Nudging fisheries and aquaculture research towards food systems - Simmance, Fiona A.; Cohen, Philippa; Huchery, Cindy; Sutcliffe, Sarah; Suri, Sharon (Wiley, 2022)
Food system is a powerful concept for understanding and responding to nutrition and sustainability challenges. Food systems integrate social, economic, environmental and health aspects of food production through to consumption. Aquatic foods are an essential part of food systems providing an accessible source of nutrition for millions of people. Yet, it is unclear to what degree research across diverse disciplines concerning aquatic foods has engaged food systems, and the value this concept has added. We conducted a systematic review of fisheries, aquaculture and aquatic food literature (2017–2019) to determine the following: the characteristics of this research; the food systems components and interrelations with which research engaged; and the insights generated on nutrition, justice, sustainability and climate change. Sixty five of the 88 reviewed articles focussed on production and supply chains, with 23 considering human nutrition. Only 13% of studies examined low- and middle-income countries that are most vulnerable to undernutrition. One third of articles looked beyond finfish to other aquatic foods, which illuminated values of local knowledge systems and diverse foods for nutrition. When aggregated, reviewed articles examined the full range of food system drivers—biophysical and environmental (34%), demographic (24%) and socio-cultural (27%)—but rarely examined interactions between drivers. Future research that examines a diversity of species in diets, system-wide flows of nutrients, trade-offs amongst objectives, and the nutritional needs of vulnerable social groups would be nudging closer to the ambitions of the food systems concept, which is necessary to address the global challenges of equity, nutrition and sustainability.